Reading Between the Lines: Narrative Accounts of How English Literature Students Construct Meaning, Navigate Misconceptions, and Make Sense of Facts and Opinions in Scientific Texts - Arman Arman; Fina Amalia Masri Fina; Neil Amstrong Neila; Rahmawati Rahmawati; Zelio da Conceicao Freitas (International Journal of Educational Narratives, 2026)
Background: The ability to distinguish between fact and opinion is a critical component of academic literacy and scientific reasoning, particularly in the digital age where students encounter complex information flows. However, misconceptions and reliance on intuition are common among higher education students, undermining critical evaluation of scientific claims. Purpose: This study aims to analyze the abilities of English Literature students at Halu Oleo University in classifying facts and opinions, and to identify factors influencing this process. Method: A mixed-methods design was employed, involving a questionnaire completed by 82 students and an argumentative analysis of their written responses based on Toulmin’s model. Quantitative data were analyzed using descriptive statistics, while qualitative data were thematically coded to assess claim construction, warrant application, use of evidence, and consideration of rebuttals. Results: The results of the study show that students tend to rely on intuition, everyday empirical experience, and common sense. sense compared to critical evaluation based on scientific evidence in determining facts and opinions. Furthermore, students’ abilities in constructing claims, providing warrants, using scientific evidence, and considering rebuttals are still relatively low. This study also found that low levels of critical digital literacy affect students’ ability to verify information and recognize digital information bias. Conclusion: These findings highlight the urgent need to strengthen epistemological literacy, argumentative skills, and digital critical literacy in academic curricula to improve students’ scientific reasoning and information evaluation capabilities.